Pengaruh Pelatihan Berbasis Kompetensi Guru Pendidikan Agama Islam Terhadap Prestasi Belajar Siswa di SMPN 1 Tanjung Pur - Satria Wiguna; Ramadayanti Saputri; Muhammad Supawi (CV. PUSDIKRA MITRA JAYA, 2025)
This study aims to analyze the effect of competency-based training attended by Islamic Religious Education (PAI) teachers on students’ learning achievement at SMP Negeri 1 Tanjung Pura. The background of this research is based on the low average scores in PAI subjects and the lack of teacher participation in practical and sustainable training programs. This study employed a quantitative approach with a correlational method. The research sample consisted of four PAI teachers and fifty-seven seventh-grade students selected proportionally from a total of 190 students. The research instruments included a teacher questionnaire to measure the implementation of competency-based training and a student questionnaire to assess PAI learning achievement. Data were analyzed using simple linear regression with the aid of the SPSS program. The results indicate that competency-based training has a significant positive effect on improving students’ learning achievement. This influence is reflected in the increased student participation in learning activities, better understanding of religious materials, and higher academic performance in PAI subjects. These findings suggest that training programs designed to be contextual, practice-oriented, and aligned with teachers’ real needs can effectively enhance the quality of learning and student outcomes. Therefore, competency-based training should be adopted as a primary strategy for developing the professional capacity of PAI teachers at the secondary school level.